About vector graphics on Latex articles - Sulca Paredes, Teodoro (2022)
Because the vast majority of scientific articles or papers that we can exchange with researchers use the program LATEXas a word processor main text, the objective of this work is that the reader knows how to generate vector graphics and insert them into his LATEXdocument. To do this, this article lists and demonstrates various techniques and tools that will allow you to achieve this goal. The combined use of programs such as Inkscape, Python and Tikz will show that the results for the graphics are of high quality since there is no loss of resolution when zooming in on the figures. It is known that the graphics in research articles illustrate what is stated in the theoretical aspect helping to transmit complex ideas in a more effective way, because a good and high quality graphic is worth more than a thousand words.